Enhancing Executive Functions in Pediatric Epilepsy: Feasibility and Efficacy of a Computerized Cognitive Training Program - José Luis Tapia; Luis Miguel Aras; Jon Andoni Duñabeitia (MDPI AG, 2024)
Epilepsy, a prevalent neurological disorder characterized by recurrent seizures, significantly impacts individuals' neurobiological, cognitive, and social lives. This report presents a feasibility study investigating the effects of a computerized cognitive training program on enhancing executive functions, particularly inhibitory control, in children and adolescents with epilepsy. Employing a pre-test-intervention-post-test design, the study involved 26 participants with diverse epileptic syndromes, focusing on those without severe intellectual disabilities. The intervention, based on the CogniFit Inc. platform, consisted of personalized tasks aiming to improve participants' inhibitory skills over 16 weeks, with an average of 40 sessions completed per participant. Results indicated significant improvements in reaction times and error rates in an anti-saccade task, demonstrating enhanced inhibitory control and general performance post-intervention. These findings suggest that targeted cognitive training is a feasible approach to bolster executive functions in young individuals with epilepsy, potentially improving their academic performance, employability, and social interactions. The study underscores the importance of early cognitive interventions in epilepsy management, highlighting the potential for computerized programs to aid in mitigating cognitive deficits associated with the condition.